Quantum coherent plasmon in silver nanowires: a real-time TDDFT study - Ding, Feizhi; Guidez, Emilie B.; Aikens, Christine M.; Li, Xiaosong (My University, 2014)
A plasmon-like phenomenon, arising from coinciding resonant excitations of different electronic characteristics in 1D silver nanowires, has been proposed based on theoretical linear absorption spectra. Such a molecular plasmon holds the potential for anisotropic nanoplasmonic applications. However, its dynamical nature remains unexplored. In this work, quantum dynamics of longitudinal and transverse excitations in 1D silver nanowires are carried out within the real-time time-dependent density functional theory framework. The anisotropic electron dynamics confirm that the transverse transitions of different electronic characteristics are collective in nature and oscillate in-phase with respect to each other. Analysis of the time evolutions of participating one-electron wave functions suggests that the transverse transitions form a coherent wave packet that gives rise to a strong plasmon resonance at the molecular level.
Keywords: Silver nanowires; Plasmon; Surface plasmon resonance; Anisotropic electron dynamics